Pregnenolone 16α-carbonitrile negatively regulates hippocampal cytochrome P450 enzymes and ameliorates phenytoin-induced hippocampal neurotoxicity - Shuai Zhang; Tingting Wang; Ye Feng; Fei Li; Aijuan Qu; Xiuchen Guan; Hui Wang; Dan Xu (Elsevier, 2023)
The central nervous system is susceptible to the modulation of various neurophysiological processes by the cytochrome P450 enzyme (CYP), which plays a crucial role in the metabolism of neurosteroids. The antiepileptic drug phenytoin (PHT) has been observed to induce neuronal side effects in patients, which could be attributed to its induction of CYP expression and testosterone (TES) metabolism in the hippocampus. While pregnane X receptor (PXR) is widely known for its regulatory function of CYPs in the liver, we have discovered that the treatment of mice with pregnenolone 16α-carbonitrile (PCN), a PXR agonist, has differential effects on CYP expression in the liver and hippocampus. Specifically, the PCN treatment resulted in the induction of cytochrome P450, family 3, subfamily a, polypeptide 11 (CYP3A11), and CYP2B10 expression in the liver, while suppressing their expression in the hippocampus. Functionally, the PCN treatment protected mice from PHT-induced hippocampal nerve injury, which was accompanied by the inhibition of TES metabolism in the hippocampus. Mechanistically, we found that the inhibition of hippocampal CYP expression and attenuation of PHT-induced neurotoxicity by PCN were glucocorticoid receptor dependent, rather than PXR independent, as demonstrated by genetic and pharmacological models. In conclusion, our study provides evidence that PCN can negatively regulate hippocampal CYP expression and attenuate PHT-induced hippocampal neurotoxicity independently of PXR. Our findings suggest that glucocorticoids may be a potential therapeutic strategy for managing the neuronal side effects of PHT.